PERCIKAN PEMIKIRAN PENDIDIKAN HAMKA - Muhammad Nasihuddin (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
One of the figures who are aware of the importance of education with interaction in the dynamics and environmental realities are Hamka. Based on studies that have been conducted using the method of literature study note that the concept of education HAMKA has five aspects of the main components of Islamic education that educators, subject matter, methods of education, students, and educational purposes.Application components such education is teachers have a noble task. To fulfill the duties of teachers should try to imitate God's nature within the limits of humanity, Islamic educational materials based on the Koran and the hadith which includes the teachings of faith, morality, science, and charity.According to Hamka, Islamic education method must have a value flexibility based on three principles, namely wisdom, mauidzah hasanah, and Mujadalah, while pupils, students HAMKA position as being a strong, active, and creative separately developed all their potential. Keywords: Hamka, education, and value